2017
DOI: 10.9790/1959-0603035665
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of hand and foot massage on alleviating pain and anxiety of abdominal post-operative patients at a University Hospital: A randomized control trial

Abstract: ABSTRACT:Background: Controlling and relieving acute postoperative pain is one of the nurses ' vital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
6
0
3
Order By: Relevance
“…Koraş and Karabulut (2018) examined the effects of foot massage performed on patients undergoing laparoscopic cholecystectomy on their pain and anxiety levels, and the postoperative state anxiety score of the experiment group was found to be lower than that in the control group (12). In a study with 60 patients (36.7% of whom underwent cholecystectomy) who had undergone abdominal surgery, similarly, there was no difference between the basal anxiety levels of the experiment and control groups, and the anxiety level was lower in the foot massage group after the third application (35). In another study conducted with patients who had undergone digestive system surgery, it was stated that there was no difference between the baseline anxiety levels of the experiment and control groups, as well as finding a decrease in the anxiety levels of the experiment group after the intervention (19).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Koraş and Karabulut (2018) examined the effects of foot massage performed on patients undergoing laparoscopic cholecystectomy on their pain and anxiety levels, and the postoperative state anxiety score of the experiment group was found to be lower than that in the control group (12). In a study with 60 patients (36.7% of whom underwent cholecystectomy) who had undergone abdominal surgery, similarly, there was no difference between the basal anxiety levels of the experiment and control groups, and the anxiety level was lower in the foot massage group after the third application (35). In another study conducted with patients who had undergone digestive system surgery, it was stated that there was no difference between the baseline anxiety levels of the experiment and control groups, as well as finding a decrease in the anxiety levels of the experiment group after the intervention (19).…”
Section: Discussionmentioning
confidence: 83%
“…Although there was no significant difference between the pain levels of the experiment and control groups before the massage intervention in the studies by Youssef and Hassan (2017) (N=60) and Chanif (2012) (N=40) among patients who underwent abdominal surgery, it was reported that the degree of pain reduction was significantly greater than that in the control group (35,36).…”
Section: Discussionmentioning
confidence: 87%
“…Ameliyat sonrası erken dönemde yetersiz ağrı tedavisi pulmoner fonksiyon bozukluklarına neden olmaktadır (17)(18)(19). Hasta ağrısının artacağı korkusu ile derin solunum yapamayıp yüzeyel ve hızlı solunum yapmaktadır.…”
Section: Ameliyat Sonrası Ağrıunclassified
“…Farmakolojik yöntemlerin solunum depresyonu, bulantı, kusma, konvülsiyon, kaşıntı, gastrointestinal motilitenin azalması, idrar retansiyonu gibi komplikasyonları (31-34) göz önüne alındığında yan etkileri olmayan nonfarmakolojik yöntemler önem kazanmaktadır (12,13). Bu yöntemlerden biri olan ayak masajı ameliyat sonrası ağrı yönetiminde kullanılabilmektedir (17,(35)(36)(37).…”
Section: Ameliyat Sonrası Ağrıunclassified
See 1 more Smart Citation